Pelatihan Pengelolaan Sampah Rumah Tangga menjadi Pupuk Organik (Stool) untuk Ibu-Ibu PKK Desa Sidemen, Lombok Barat - Rusdi, Ahyar; Fajrin, Muhammad (Journal of Community Development and Empowerment, 2025)
Household waste is one of the growing environmental issues, especially in rural areas. One potential solution is processing household waste into organic fertilizer, which is beneficial for agriculture and plants. The aim of this training was to provide knowledge and skills to the women of the PKK group in Sidemen Village, West Lombok, on how to manage household waste into organic fertilizer (stool). The training activities involved both theoretical and practical methods, where participants were introduced to the types of waste that can be processed, as well as efficient and eco-friendly techniques for producing organic fertilizer. The results of the training showed that the women of the PKK in Sidemen Village were able to implement household waste processing techniques into organic fertilizer that can support food security in their environment. It is hoped that this training not only reduces the amount of waste disposed of but also increases awareness of the importance of sustainable waste management.